Pola pemahaman agama Islam dan pengembangan kependidikan - Kontribusi Rasyid Ridha - Alamsyah, Anas Amin (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2016)
Rashid Rida is Muslim figures who have gait significant and substantial contribution in the process of reform in the Islamic world. His ideas are quite brilliant in fighting the Muslims to be able to rise from their setback. Reforming movement that does become more stable by giving conceptions about various aspects of science that became an important discourse at the time. After the proposed reforming ideas and concepts of the caliphate in view of Rashid Rida, it can be taken a couple of conclusions. In the field of religion, Rashid Rida calls on Muslims to re-understand and practice the teachings of Islam. In the field of education, Rashid Rida states that if Muslims want to move forward then they must accept the Western civilization is based on advances in science and technology. To take on Western civilization, Muslims should be through education in which science and technology are taught. In politics, Muslims must be able to enforce unity on dar same belief, namely the unity of Muslims. While in the field of the caliphate (the leadership), Rashid Rida advocated the establishment of the state in the form of Caliphate ruled by a caliph who held the answers to the advancement of religion and the world